Preparation of pervaporation membrane using a-type zeolite filled chitosan membrane for the separation of isopropanol/water mixtures - Saim, Nursharina (Penerbit UTM Press, 2008)
The novel polymeric membranes were prepared by incorporating the NaA zeolite into chitosan and were subjected for the pervaporation separation of water-isopropanol mixtures. The resulting membranes were characterized by Fourier transform infrared spectroscopy (FTIR). The effects of zeolite loading and feed composition on the pervaporation performance of the membranes were analyzed. The membranes were tested for its mechanical properties in terms of tensile strength, elongation and Young’s Modulus. The incorporated membrane showed an increase in strength and elongation until it reached its optimum value of 0.3 weight % of zeolite loading in the membrane. The experimental results showed that both flux and selectivity increased with the addition of zeolite content in the membrane. This was explained on the basis of enhancement of hydrophilicity, selective adsorption and molecular sieving action by creation of pores in the membrane matrix.